2022
DOI: 10.1021/acscatal.1c05676
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Promotion Effects of Dynamically Constructed CuOx-OH Interfacial Sites in the Selective Catalytic Oxidation of Ammonia

Abstract: The selective catalytic oxidation of ammonia (NH3-SCO) into N2 and H2O is a recognized effective protocol to eliminate excessive NH3 emission. Nevertheless, it is a great challenge for NH3-SCO catalysts to balance the NH3 oxidation activity with N2 selectivity. Herein, promotion effects of the dynamically constructed CuO x -OH interfacial sites for NH3 oxidation activity without the scarification of N2 selectivity were unraveled. The enrichment of coordination unsaturated Cu sites and Cu-OH acid sites in CuO x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…10 wt.% as an optimum loading of copper species [4]. The full NH 3 conversion of this group appears at 350-500 • C with N 2 selectivity above 75% (Table 2) depending on the preparation methods (e.g., copper precursors [70,72], treatment strategies [9]), and reaction conditions (e.g., fuel-lean/rich conditions [71,73,74]). Based on the studies of Lenihan and Curtin [69], the stability of Cu/Al 2 O 3 through the dry, wet and subsequently dry conditions was proved.…”
Section: Other Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…10 wt.% as an optimum loading of copper species [4]. The full NH 3 conversion of this group appears at 350-500 • C with N 2 selectivity above 75% (Table 2) depending on the preparation methods (e.g., copper precursors [70,72], treatment strategies [9]), and reaction conditions (e.g., fuel-lean/rich conditions [71,73,74]). Based on the studies of Lenihan and Curtin [69], the stability of Cu/Al 2 O 3 through the dry, wet and subsequently dry conditions was proved.…”
Section: Other Metal Oxidesmentioning
confidence: 99%
“…Depending on the applied treatment (calcination versus dynamic construction), NH 3 -SCO over the catalysts can follow different routes. For example, the fast i-SCR mechanism characterized by the presence of consumable NO 2 adsorbed species was proposed on CuO x -OH interfacial sites [ 9 ]. Still, compared to NH 3 -SCR-DeNO x , the reaction mechanisms of NH 3 -SCO are not frequently discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…14,29,38−42 By means of H 2 -calcination followed by dynamic construction in a reaction mixture, Lan et al fabricated coordinatively unsaturated CuO x -OH sites on the interface of a Cu/Al 2 O 3 catalyst and achieved a 9-fold increase in NH 3 oxidation rate and a 40 kJ/mol decrease in apparent activation energy compared with the conventional CuO sites. 41 Hinokuma et al demonstrated that the local structures, reducibility, and, consequently, NH 3 -SCO performance of the supported CuO x particles can be regulated by thermal aging (above 900 °C) or compositing with Al 2 O 3 . 43 In this regard, nitrogen-doped carbon nanotubes (NCNTs) are particularly promising as catalyst supports because the interactions between the metal phase and the NCNT support can be easily tuned by controlling the type and amount of nitrogen groups on the carbon surface.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, modulating the interactions between the Cu sites and the support materials (most commonly alumina, zeolites, ceria, mixed Zr-Ce oxides, carbons, etc. ) has proven to be another effective yet economical approach to boost the catalytic performance of Cu catalysts. ,, By means of H 2 -calcination followed by dynamic construction in a reaction mixture, Lan et al . fabricated coordinatively unsaturated CuO x -OH sites on the interface of a Cu/Al 2 O 3 catalyst and achieved a 9-fold increase in NH 3 oxidation rate and a 40 kJ/mol decrease in apparent activation energy compared with the conventional CuO sites .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation